"International Public Law", by Oscar Maúrtua de Romagna (Coordinator) - Peruana de Derecho Internacional, Sociedad (2020)
Since José María de Pando published in 1827 his work Elements of LawInternational, the edition of works on the subject has gone with time becoming morelimited. For this reason, in our times in which globalization demands newhorizons to international studies, the appearance of this work entitled LawInternational Public, under the coordination of Ambassador Oscar Maúrtua, President ofthe Peruvian Society of International Law, is a good news and an investigationthat stimulates the national legal community.